Coaxiality detection method with non-adjustment for installation errors. (7th April 2020) - Xin, Jin; Zhang, Qiushuang; Shang, Ke; Pu, Yimin; Zhang, Zhijing; Guo, Huan
During the assembly of the engine casing, the coaxiality detection for the two assemblies are essential. And the modern manufacturing industry has put forward higher requirements for the coaxiality measurement with the development of the industrial technology. The existing coaxiality detection methods are mostly based on manual measurements. It takes long time to adjust the axes of assembly parts and turntable to coincide by the current measurement method, which greatly affects production efficiency. To solve the problem, this paper proposes a coaxiality detection method which can compensate assembly installation errors automatically. The coaxiality measurement method based on the position of the assembly is deduced by introducing the measurement mechanism of the coordinate measuring machine. The data processing uses coordinate transformation and least squares fitting method. Experimental verification shows that the method does not need to adjust the assembly part repeatedly, so measuring time is reduced greatly. The methods simplify the measurement steps and provide supports of methods and techniques for automatic detect.